Tinjauan Filosofis tentang Epistemologi Usul Fikih Berbasis Metode Jama’i - Hasan Bisri (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2020)
This article attempts to offer the jama’i method as one of the epistemologies of ushul fiqh. The offer is based on the idea that the fiqh proposal philosophically contains various views, at least from an epistemological point of view. The epistemology that develops in the intellectual journey of Muslims is not as simple as people imagine. In recent developments, it seems that the epistemology of the fiqh proposal has received little attention or even wants to be dumped on the grounds of fear of the destruction of the fiqh proposal itself; at least, it still gets a reasonably enthusiastic response from fiqh experts. Thus, it becomes very natural when the reviewers of fiqh proposals in various Islamic universities are required to constantly innovate and explore the idea of fiqh proposals as Islamic logic. In this article, the author offers Jamaican epistemology.